Tinjauan Hukum Ekonomi Syariah Terhadap Praktik Gaduh Sapi : (Studi Kasus Di Desa Cumedak Kecamatan Sumberjambe) - Mohammad Firmansyah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
The practice of rowdy cows is a form of cooperation between cattle owners and cattle managers as a side job by managing other people's livestock in exchange for profit sharing. The focus of research in this thesis is how to review sharia economic law on the practice of rowdy cows and how to review sharia economic law against unilateral cancellations in the practice of rowdy cows. The purpose of this study was conducted to find out about how Islamic economic law reviews the practice of rowdy cows and reviews of Islamic economic law against unilateral cancellations in the practice of rowdy cows. The writing method in this thesis is a qualitative method that is describing objects systematically. Data and data sources used in this study are primary data sources and secondary data sources. Data collection techniques using observation, interviews and documentation. How is the review of sharia economic law on the practice of rowdy cows researchers concluded that the practice of rowdy cows in Cumedak village is a form of cooperation which is only an additional job, the contract is carried out orally and the capital is in the form of cows and bulls. Profits are divided into two, namely in the form of calves, and in the form of money. This contract is harmonious and the conditions have been fulfilled. What is the review of sharia economic law on unilateral cancellations in the practice of rowdy cows? researchers conclude that unilateral contract cancellations here fall into the category of ja'iz contracts, namely transactions that are not binding and are always open to unilateral cancellation. Permission to cancel the contract can occur when there is betrayal from one of the parties.